Synthesis and Antibacterial Activity of Coumarin and Its Derivatives - Ali, Zulfiqar; Naman Khalid, Mirza; Rubina Gilani, Syeda; Hussain, Habib; Rehman, Hajira; Hussain, Imdad; Sadiqa, Ayesha (Asian Journal of Chemistry, 2015)
Coumarin and its different derivatives were prepared by treating ethyl acetoacetate with phenol and its different derivatives in acidic media. Product formation was confirmed by spectroscopic techniques i.e. IR, NMR etc. The antimicrobial activities of synthesized compounds were checked against different gram positive and gram negative bacteria by agar ditch method.